Age Dependence of Antimicrobial Resistance Among Fecal Bacteria in Animals: A Scoping Review - Gaire, Tara N.; Scott, Harvey Morgan; Sellers, Laura; Nagaraja, T. G.; Volkova, Victoriya V. (Frontiers in Veterinary Science, 2021)
Introduction: A phenomenon of decreasing antimicrobial resistance (AMR) among fecal bacteria as food animals age has been noted in multiple field studies. We conducted a scoping review to summarize the extent, range, and nature of research activity and the data for the following question: “Does AMR among enteric/fecal bacteria predictably shift as animals get older?” Methods: This review followed a scoping review methodology framework. Pertinent literature published up until November 2018 for all animals (except humans) was retrieved using keyword searches in two online databases; namely, PubMed® and the Web of ScienceTM Core Collection, without filtering publication date, geographical location, or language. Data were extracted from the included studies, summarized and plotted. Study quality was also assessed using GRADE guidelines for all included papers. Results: The publications with detailed relevant data (n=62) in food animals, poultry, and dogs were identified. These included longitudinal studies (n=32), cross-sectional studies of different age groups within one food animal production system or small-animal catchment area (n=16), and experimental or diet trials (n=14). A decline in host-level prevalence and/or within-host abundance of AMR among fecal bacteria in production beef, dairy cattle, and swine was reported in nearly two-thirds (65%) of the identified studies in different geographic locations from the 1970s to 2018. Mixed results, with AMR abundance among fecal bacteria either increasing or decreasing with age, have been reported in poultry (broiler chicken, layer, and grow-out turkey) and dogs. Conclusions: Quantitative synthesis of the data suggests that the age-dependent AMR phenomenon in cattle and swine is observed irrespective of geographic location and specific production practices. It is unclear whether the phenomenon predates or is related to antimicrobial drug use. However, a majority of the identified studies predate recent changes in antimicrobial drug use policy and regulations in food animals in the United States and elsewhere.